Coping with Life during the Thirty Years' War (1618-1648) - Haude, Sigrun, author.
1 online resource.
Keywords: At its core, Coping with Life during the Thirty Years' War (1618-1648) explores how people tried to survive the Thirty Years' War, on what resources they drew, and how they attempted to make sense of it. A rich tapestry of stories brings to light contemporaries' trauma as well as women and men's unrelenting initiatives to stem the war's negative consequences. Through these close-ups, Sigrun Haude shows that experiences during the Thirty Years' War were much more diverse and often more perplexing than a straightforward story line of violence and destruction can capture. Life during the Thirty Years' War was not a homogenous vale of gloom and doom, but a multifaceted story that was often heartbreaking, yet, at times, also uplifting.